Cost analysis and price variation of commonly used drugs in obstetrics and gynecology in Jhalawar district of Rajasthan, India - Jhanwar, Anshul; Sharma, Neelam (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drugs used in obstetrics and gynecology are strong selling drugs in pharmaceutical market but they are the least studied drugs in terms of cost analysis and price variation. Methods: Cost of most commonly used Obstetrics and Gynecology drugs in Jhalwar district manufactured by different pharmaceutical companies, in the same strength and dosage forms was obtained from Drug Today (January-March 2018). The difference in the maximum and minimum price of the same drug manufactured by different pharmaceutical companies and percentage variation in cost per 10 tablets/10 capsule/1 injection/1 protein packet/1 sachet were analysed. Results: In Obstetrics drugs, the highest cost ratio (1:9.5) and percentage price variation (848) was found for Ferrous Salt + Folic acid combination followed by Cefixime (1:4.3, 330), Nifedipine (1:3.7, 270), Folic acid (1:3.67, 266), Paracetamol. Amoxicillin was having least cost ratio (1:1.4) and percentage price variation (37). Maximum number of brand available for Ferrous Salt + Folic acid combination (41) followed by Paracetamol, Calcium Salt + Vitamin D3 combination. In Gynecological drugs, the highest cost ratio (1:35) and percentage price variation (3433) was found for Ethinylestradiol + Levonorgetral combination followed by Doxycycline (1:8.9, 793), Fluconazole. Metronidazole was having least cost ratio (1:1.3) and percentage price variation (27). Maximum number of brand available for Omeperazole (27) followed by Ethamsylate (22). Conclusions: This study shows that the average percentage price variation of different brands of the same drugs were very wide. Improved adherence to the drug treatment can be ensured by decreasing the cost of therapy, which can be done by changes in the government policies and regulations, integrating pharmacoeconomics as part of medical education curriculum, and creating awareness among treating physicians for switching to cost effective therapy.